Incidence of Bemisia tabaci Gennadius (Aleyrodidae, Aleyrodinae) in four Atlantic Forest fragments - Trindade,Thiago Dias (2019)
ABSTRACT: Bemisia tabaci has been known in Brazil since 1923, in cotton, soybean, tomato and bean crops, and it leads to economic losses due to the transmission of different viruses. Studies focused on analyzing the incidence of this pest in forest environments remain scarce in the literature. Thus, the aims of the current study were to investigate the incidence of B. tabaci in four Atlantic forest fragments in Rio de Janeiro state, Brazil, as well as to record its hosts in these environments. An area of approximately one hectare was delimited for each Atlantic forest fragment based on images provided by the Brazilian Institute of Geography and Statistics (IBGE). Plants presenting whiteflies were tagged throughout monthly inspections conducted in each forest fragment in order to be checked during the following visits. Collection criteria were adopted to assure sampling standardization in each fragment. The mean number of whiteflies was analyzed through the Kruskal-Wallis non-parametric test, which was followed by Dunn’s post-hoc test, both at 5% significance level. The total of 216 collections were conducted and 1,126 B. tabaci fourth-instar nymphs were collected in four Atlantic forest fragments over 24 months. The following hosts were recorded for the first time: Caesalpinia pluviosa Benth, Tradescantia zebrina Linn., Impatiens walleriana Linn., Cupania sp. and Talisia esculenta Klotzsch & O. Berg. The dry period (winter) enabled the increase of B. tabaci populations in the herein investigated forest fragments.